DYNAMICS OF IMMUNOLOGIC INDICES IN DISEASES OF BACTERIAL ETIOLOGY AND THE CORRECTION OF IMMUNE STATUS OF CALVES - I.A. Kondakova (Journal of Global Pharma Technology, 2016)
Compensation of defects of intestinal tract colonization resistance during correction of immune status of calves with the help of phytogenic medicinal preparations was characterized by an increase in the total amount of T-lymphocytes, T-helpers, relative content of B-lymphocytes and level of IgG, IgM, IgА with a simultaneous growth of phagocytic index and phagocytic activity of neutrophils. Keywords: Diseases of bacterial etiology, Young stock of farm animals, Immune correction, pine buds, Propolis.